Critical posthumanism, new materialisms and the affective turn for socially just pedagogies in higher education - Bozalek, V.; Zembylas, M. (South African Journal of Higher Education, 2016)
Critical posthumanism, new/feminist materialisms and the affective turn have a great deal in common with each other, and can be seen as similar perspectives with slightly different emphases in each framework, all focusing on: relational ontologies; a critique of dualisms; and engagements with matter and the non-human. Feminist thinkers such as Rosi Braidotti, Donna Haraway, Karen Barad, Elizabeth Grosz, Nancy Tuana, Vicky Kirby, Jane Bennett,and Stacey Alaimo, amongst others, have been identified both as critical posthumanists and new/feminist materialists, and have also contributed to ideas about the affective turn. Many of these scholars have been influenced by the work of Deleuze and Guattari and their notions of monism and vitalism, and have moved beyond the centrality of discourse and cartesian dualisms to incorporate a vision of human/nonhuman, body/mind, subject/object, nature/culture, matter/meaning, continuity/discontinuity, beginning/returning and creation/renewal (Barad 2007) in their work.